2020
DOI: 10.3390/nu12102944
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between Plasma Concentrations of Vitamins C and E along the Trajectory of Ageing in Consideration of Lifestyle and Body Composition: A Longitudinal Study over Two Decades

Abstract: Although the interrelation between vitamins C and E has been demonstrated on an experimental level, its impact on biomarkers in community-dwelling subjects along the trajectory of ageing has not yet been shown. The present longitudinal study investigates the determinants and interrelation of vitamins C and E plasma concentrations in 399 subjects aged ≥60 years with a median follow-up time of 12 years. Linear mixed-effects models were used to analyze the influence of age, sex, body composition, dietary intake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…For plasma vitamin C concentrations, the use of supplements, physical activity, fat-free mass, and plasma α-tocopherol were the main determinants. Age, the use of supplements, the use of lipid-modifying drugs, and plasma vitamin C were the main determinants for the α-tocopherol/total cholesterol ratio [64]. The results emphasize the idea of an interrelation between plasma levels of vitamin C and E, and also suggest an association between physical activity and fat-free mass with vitamin C and E status.…”
Section: Supplementation With Vitamin E Alone and Combined With Vitamsupporting
confidence: 51%
See 1 more Smart Citation
“…For plasma vitamin C concentrations, the use of supplements, physical activity, fat-free mass, and plasma α-tocopherol were the main determinants. Age, the use of supplements, the use of lipid-modifying drugs, and plasma vitamin C were the main determinants for the α-tocopherol/total cholesterol ratio [64]. The results emphasize the idea of an interrelation between plasma levels of vitamin C and E, and also suggest an association between physical activity and fat-free mass with vitamin C and E status.…”
Section: Supplementation With Vitamin E Alone and Combined With Vitamsupporting
confidence: 51%
“…This vitamin E recycling requires a supply of vitamin C and is often why these nutrients will be consumed simultaneously via supplementation [ 63 ]. More recently, Jungert et al [ 64 ] investigated the determinants and interrelation between plasma concentrations of vitamin C and E in the elderly. For plasma vitamin C concentrations, the use of supplements, physical activity, fat-free mass, and plasma α-tocopherol were the main determinants.…”
Section: Vitamin E As An Antioxidant Supplementmentioning
confidence: 99%
“…Furthermore, a recent study revealed a stable positive interrelation between plasma concentrations of vitamins E along the trajectory of ageing independent of the other identified determinants. 16 Therefore, it is essential for clinical laboratories to establish RIs based on their current measurement methods, especially when these values are applied to the elderly population. In this study, vitamin A and E levels in fasting serum samples were measured to reflect the individual's reserve status.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, we developed an accurate and reliable LC‐MS/MS method for establishing vitamin A and E RIs that can be used in the clinical setting. Furthermore, a recent study revealed a stable positive interrelation between plasma concentrations of vitamins E along the trajectory of ageing independent of the other identified determinants 16 . Therefore, it is essential for clinical laboratories to establish RIs based on their current measurement methods, especially when these values are applied to the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitamin C deficiency is more prevalent in older populations [21,22]. Because the older population has higher requirements for vitamin C, it is particularly important for older adults to obtain an adequate daily vitamin C intake [23,24].…”
Section: Introductionmentioning
confidence: 99%